Persepsi Mahasiswa terhadap Dosen dalam Mengajar di Fakultas llmu Komunikasi Universitas Prof. Dr. Moestopo (Beragama) - Sunarto, Sunarto; Syahudi, Giman; Erland, Radja (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
This research of background overshadow by existence of some problems of arisingout in course of study  like for example less obedient the lecturer to discipline teach and less precisely instruction method  used by some lecturer, this matter   have opportunity to generate impact of student, by unfavourable  ways of lecturer in teaching to generate ugly perception among student to lecturer,so that in the end will affect at degradation of education quality.Pursuant to  the  background hence  problems  which   lifted in this research is  "  How perception Student  to  Lecturer of  teaching in  Faculty of  Communications Science, Universityof  Prof Dr.  Moestopo (Beragama)? To solve the problems of researcher use theory A. Devito Learning Education Processand of Persepsion Process, Theory Cognitive of DavidA. Aeker and theory of nature and also perception element  from Sasa Djuarsa Sendjaja. As for Conceptualization of approach the theory is that things required to dug from perception of Student cover appearance of lecturer teach, compliance of lecturer to discipline teach, teach method, domination to lesson items and the also domination of class..